KCa3.1 channel mediates inflammatory signaling of pancreatic β cells and progression of type 2 diabetes mellitus. Issue 12 (5th November 2019) - Pang, Zheng‐Da; Wang, Yan; Wang, Xiao‐Jing; She, Gang; Ma, Xiao‐Zhen; Song, Zheng; Zhao, Li‐Mei; Wang, Hui‐Fang; Lai, Bao‐Chang; Gou, Wei; Du, Xiao‐Jun; Deng, Xiu‐Ling
Abstract : Chronic islet inflammation is associated with development of type 2 diabetes mellitus (T2DM). Intermediate‐conductance calcium‐activated K+ (KCa 3.1) channel plays an important role in inflammatory diseases. However, the role and regulation of KCa 3.1 in pancreatic β cells in progression of T2DM remain unclarified. In the present study, we evaluated the effect of the specific KCa 3.1 channel blocker 1‐[(2‐chlorophenyl)diphenylmethyl]‐1H‐pyrazole (TRAM‐34) on diabetic phenotype in the db/db model. In diabetic mice, blockade of KCa 3.1 significantly improved glucose tolerance, enhanced secretion of postprandial insulin level, and reduced loss of β‐cell mass through attenuating the expression and secretion of inflammatory mediators. Furthermore, in cultured pancreatic β cells, exposure to high levels of glucose or palmitic acid significantly increased expression and current density of the KCa 3.1 channel as well as secretion of proinflammatory chemokines, and the effects were similarly reversed by preincubation with TRAM‐34 or a NF‐κB inhibitor pyrrolidinedithiocarbamate. Additionally, expression of KCa 3.1 in pancreas islet cells was up‐regulated by activation of NF‐κBwithIL‐1β stimulation. In summary, up‐regulated KCa 3.1 due to activation of NF‐κB pathway leads to pancreatic inflammation via expression and secretion of chemokines and cytokines by pancreatic β cells, thereby facilitating progression of T2DM.—Pang, Z.‐D., Wang, Y., Wang, X.‐J., She, G., Ma, X.‐Z., Song, Z., Zhao, L.‐M., Wang, H.‐F., Lai, B.‐C., Gou, W., Du, X.‐J., Deng, X.‐L. KCa 3.1 channel mediates inflammatory signaling of pancreatic β cells and progression of type 2 diabetes mellitus. FASEB J. 33, 14760‐14771 (2019). www.fasebj.org